Asteroseismology of Massive Stars: Some Words of Caution. Issue Volume 9:Issue S307(2014) (23rd January 2015) - Noels, A.; Godart, M.; Salmon, S. J. A. J.; Gabriel, M.; Montalbán, J.; Miglio, A.
Abstract: Although playing a key role in the understanding of the supernova phenomenon, the evolution of massive stars still suffers from uncertainties in their structure, even during their "quiet" main sequence phase and later on during their subgiant and helium burning phases. What is the extent of the mixed central region? In the local mixing length theory (LMLT) frame, are there structural differences using Schwarzschild or Ledoux convection criterion? Where are located the convective zone boundaries? Are there intermediate convection zones during MS and post-MS phase, and what is their extent and location? We discuss these points and show how asteroseismology could bring some light on these questions.